Analisis Jaringan Komunikasi Percakapan #tetapdukungpsbb di Twitter pada Penerapan PSBB Kedua DKI Jakarta - Ahmad Fatoni; Pricilla Anestha (LPPM Stikosa - AWS, 2020)
This study aims to determine the level of the system, actors in the PSBB Total Jakarta conversation communication network on Twitter, and the contents of the conversation on Twitter about PSBB Total Jakarta which was reintroduced on September 14, 2020. This research method is quantitative with social network analysis techniques, visualization of the network will be in the form of a graph. This research will use a realist approach with a population of netizens from Twitter who have activity on the hashtag #TetapDukungPSBB with 1000 tweets taken on September 14, 2020, on an unpaid netlytic.com account, the results of crawling data will be limited to 1000 tweets and data retrieval in the past 2 weeks. The results of this study show that the system-level communication network in the #TetapDukungPSBB conversation has a diameter of 16 points. The network has a slow deployment, with dominant tweets having no reciprocity, no dominance of actors on information flow, and consisting of a core group of nodes. At the actor level, 5 accounts are considered as a popular actor. There are 1 account intermediary relations on this network that can connect one account to another to communicate with each other. In this network, actors can be said to be quite free in communicating and 5 actors are considered important in the network. Discussions on the network tend to discuss other matters and support the re-enactment of the PSBB.